Attrition-induced spontaneous chiral amplification of the γ polymorphic modification of glycine1. Issue 7 (21st February 2015) - Tarasevych, Arkadii V.; Sorochinsky, Alexander E.; Kukhar, Valery P.; Toupet, Loïc; Crassous, Jeanne; Guillemin, Jean-Claude
<x xml:space="preserve">Abstract</x> Glycine is the simplest achiral amino acid that undergoes spontaneous mirror symmetry and controlled deracemization in its γ-polymorphic modification.